2022
DOI: 10.21037/hbsn-21-419
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of hepatocellular carcinoma patients with macrovascular invasion following surgical resection: a meta-analysis of 40 studies and 8,218 patients

Abstract: Background: Guidelines recommend that hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT) and/or hepatic vein tumor thrombosis (HVTT) should undergo systemic therapy.However, recent data suggest that surgical resection may be beneficial in selected cases, but outcomes are heterogenous. We aimed to estimate pooled overall survival (OS), recurrence free survival (RFS) and complication rates in HCC patients with macrovascular invasion (MVI) following surgical resection.Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Systemic chemotherapy, EBRT, or a combination of both are preferred. 32 , 33 A recent study concluded that combined TACE and radiation therapy (RT), rather than systemic treatment alone, may be considered as a first-line treatment option for patients with HCC and macrovascular invasion. 34 A previous randomized controlled trial and systematic review reported that neoadjuvant RT provided significantly better post-operative survival outcomes than surgery alone in patients with resectable HCC and PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy, EBRT, or a combination of both are preferred. 32 , 33 A recent study concluded that combined TACE and radiation therapy (RT), rather than systemic treatment alone, may be considered as a first-line treatment option for patients with HCC and macrovascular invasion. 34 A previous randomized controlled trial and systematic review reported that neoadjuvant RT provided significantly better post-operative survival outcomes than surgery alone in patients with resectable HCC and PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related death worldwide 1,2 . Patients with HCC have a 5‐year survival of less than 20% overall 3–7 . The poor prognosis of HCC, in general, has led to increased interest in HCC prevention.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Patients with HCC have a 5-year survival of less than 20% overall. [3][4][5][6][7] The poor prognosis of HCC, in general, has led to increased interest in HCC prevention. Emerging data suggest that the use of statins, aspirin and metformin may be chemoprotective against HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Huang et al ( 8 ) presented a meta-analysis reporting clinical outcomes of surgical resection for HCC with MVI including 40 studies involving 8,218 patients. This study may have a significant clinical impact because there has never been such a sizable study before.…”
mentioning
confidence: 99%
“…According to the results of the meta-analysis, they suggested that surgical resection may be a viable alternative option in the setting of segmental or 2 nd order PVTT. Whereas, they suggested that invasive surgery should be avoided in HCC patients with 1 st order or main PVTT, given the poor OS outcomes ( 8 ).…”
mentioning
confidence: 99%